Acrylamide Capture of DNA-Bound Complexes: Electrophoretic Purification of Transcription Factors. (April 2002) - Nelson, Colleen; Hendy, Stephen; Reid, Kim; Cavanagh, John
We have developed a rapid nonradioactive electrophoretic technique to analyze proteins within DNA-binding complexes, acrylamide capture of DNA-binding complexes (ACDC), using Acrydite™-linked DNA-binding targets. The method is highly sensitive and easily adaptable to virtually any protein-DNA interaction. The utility of this technique is illustrated using recombinant and full-length androgen receptors and associated co-regulatory proteins present within nuclear extracts. In brief, proteins were incubated with DNA-binding targets in which one oligonucleotide was synthesized with an Acrydite moiety at the 5′ end to allow for covalent linkage to acrylamide. Alternatively, gene promoter regions were amplified with an Acrydite-modified PCR primer to analyze protein-DNA complexes. The DNA-binding reaction was polymerized into an acrylamide matrix within the well of a precast gel. Proteins complexed to the Acrydite DNA are trapped and purified by the electrophoretic migration of unbound proteins. Proteins captured in the Acrydite-DNA can be eluted and identified by Western analysis or 2-D gel electrophoresis. The advantages of this technique are that it is rapid, adaptable, sensitive, unlimited by the size of the DNA or protein complex, and can be used to detect tertiary interactions with co-regulatory factors and unidentified proteins. These features make the ACDC technique a powerful tool for transcription factor research.